Adversity in teacher education in Japan: Professional development or professional impoverishment? - Saito, Eisuke; Murase, Masatsugu (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2011)
This paper aims to discuss teacher education in Japan. In pre-service education, the curriculum at the Bachelor’s degree level has shifted more to an approach that emphasizes reflective practices. Professional schools of teacher education, which have recently been established for the Master’s degree level, are supposed to function as a practical course of education, but it is still very unclear how they are different from the existing graduate schools of education. In the domain of in-service training, a teacher license renewal system was recently introduced, but it does not seem to be meaningful because of its cost. Instead of the introduction of license renewal system, it is more efficient and effective for teachers to be united and involved in reforming themselves at every school level in order to create secure learning spaces and communities inside the schools.